Preservice Elementary Teachers Using Graphing as a Tool for Learning, Teaching, and Assessing Science - Gould, Deena; Robles, Rolando; Rillero, Peter (Innovations in Science Teacher Education, 2020)
Graphing is an important tool for seeing patterns, analyzing data, and building models of scientific phenomena. Teachers of elementary school children use graphs to display data but rarely as tools for analyzing or making sense of data (Coleman, McTigue, & Smolkin, 2011). We provide a set of lessons that guide preservice elementary school teachers to analyze their conceptions about graphing and use graphing to (a) see patterns in data, (b) discuss and analyze data, (c) model scientific phenomena, and (d) teach and assess inquiry-based science. Examples are adduced for how we guided and supported preservice elementary teachers in their conceptual understanding and deeper use of graphing.